THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, WORK CULTURE, AND SELF-CONCEPT ON TEACHER PERFORMANCE - MINAYATI, Minayati; Khuluqo, Ihsana El; A. GHANI, Abd. Rahman (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2025)
The purpose of this study is to analyze, and test: the influence of transformational leadership, work culture and self-concept on teacher performance in driving schools throughout Tangerang City. This study uses a causal survey method with a path analysis technique. The population in this study is all driving teachers in Tangerang City totaling 165 teachers with a sample of 117 teachers taken based on proportional random sampling. The analysis technique used is the path analysis technique. Based on the results of the analysis, it is known: 1) There is a direct positive and significant influence of transformational leadership on teacher performance; 2) There was a direct positive and significant influence of work culture on teacher performance; 3) There was a direct positive and significant influence of teachers' self-concept on teacher performance; 4) There was a direct positive and significant influence of transformational leadership on teachers' self-concept; 5) There was a direct positive and significant influence of work culture on teachers' self-concept; 6) There was a direct positive and significant influence of transformational leadership on work culture.